Pyrolysis behavior of raw/torrefied rice straw after different demineralization processes. (December 2018) - Dong, Qing; Zhang, Shuping; Ding, Kuan; Zhu, Shuguang; Zhang, Houlei; Liu, Xinzhi
Abstract: This study aims to evaluate the effects of different demineralization processes on the pyrolysis behavior and pyrolysis product properties of raw/torrefied rice straw. To achieve this target, different demineralization pretreatment processes with deionized water, acetic acid and hydrochloric acid solutions of rice straw were carried out, and the detailed information of fuel characteristics, alkali and alkaline earth metals (AAEMs) concentration, thermal degradation behavior and pyrolysis product properties were figured out. The results indicated that demineralization processes improved the fuel characteristics. The removal efficiencies of AAEMs increased in the order hydrochloric acid > acetic acid > deionized water. Torrefied samples exhibited lower removal efficiencies of AAEMs than that of raw samples because of the speciation transformations of AAEMs during torrefaction. More obvious effect of alkali metals on the pyrolysis process can also be obtained than that of alkaline earth metals. Compared with raw rice straw, the effects of demineralization processes on the changes of cellulose crystallinity of torrefied rice straw can be ignored. All the demineralization processes enhanced the bio-oil yield at the expense of biochar and non-condensable gases for raw/torrefied samples. They also have important promoting influence on the properties of bio-oil and biochar by enhancing the sugars formation and improving the fuel characteristics of biochar. The obtained results can be helpful for understanding the pyrolysis behavior of raw/torrefied rice straw after different demineralization processes and for further utilization of biomass resources with high contents of silica and potassium. Highlights: Demineralization on pyrolysis behavior of raw/torrefied rice straw was evaluated. Demineralization processes improved the fuel characteristics of rice straw. Torrefied samples exhibited lower removal efficiencies of AAEMs than raw samples. K and Na exhibited more notable effects on pyrolysis process than Ca and Mg. Demineralization has the promoting effect on bio-oil and biochar properties.